Sodium ion battery and electric equipment
By introducing an appropriate amount of surfactant into the electrolyte of the sodium ion battery, the problems of large specific surface area of the negative electrode material and poor wetting ability of the electrolyte are solved, and the high energy density and cycle stability of the battery are achieved.
Patent Information
- Application Number
- CN202410101387.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-23
- Publication Date
- 2025-04-11
AI Technical Summary
The negative electrode materials of existing sodium ion batteries have large specific surface area and multiple surface defects, which leads to the electrolyte forming thick SEI on the negative electrode surface and consumes active sodium; while the viscosity and surface tension of commercial electrolytes are large, resulting in poor pore wetting, which reduces the discharge specific capacity and energy density of the battery.
By introducing surfactant into the electrolyte, matching its hydrophilic-lipophilic equilibrium value (HLB) with the thickness and porosity of the negative electrode active material layer, the electrolyte is promoted to infiltrate the negative electrode active material layer, alleviate the risk of analyzing sodium, and improve the discharge capacity and energy density of the battery.
It improves the high energy density, high discharge specific capacity and high cycle stability of sodium ion batteries, reduces battery polarization, and improves the rate discharge capacity.
Smart Images

Figure BDA0004680767790000061 
Figure BDA0004680767790000071 
Figure BDA0004680767790000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery and electrical equipment. Background Art
[0002] Lithium-ion batteries are the most widely commercialized electrochemical energy storage devices. They achieve the conversion of chemical energy and electrical energy through the reversible insertion / extraction of lithium ions between the positive and negative electrodes. Sodium and lithium belong to the same main group, but the reserves of sodium on Earth are much higher than lithium, and my country has abundant sodium resources and sodium extraction technology, so the cost of sodium-ion batteries will be greatly reduced compared to lithium-ion batteries.
[0003] However, the negative electrode commonly used in sodium-ion batteries currently has the disadvantages of large specific surface area and many surface defects, which will cause the electrolyte to form a thicker SEI on the negative electrode surface and consume more active sodium. In addition, the electrolyte of commercial sodium-ion batteries mainly uses carbonate solvents, which have high viscosity and surface tension and poor wettability to pores, resulting in reduced battery discharge capacity and energy density. Summary of the invention
[0004] Based on this, the present invention provides a sodium ion battery and electrical equipment with high energy density, high discharge specific capacity and high cycle stability.
[0005] In a first aspect, an embodiment of the present invention provides a sodium ion battery, the sodium ion battery comprising:
[0006] A positive electrode; a negative electrode, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer is disposed on the negative electrode current collector, and wherein the thickness of the negative electrode active material layer is D1 μm and the porosity is ρ%;
[0007] An electrolyte, the electrolyte comprising a sodium salt, a solvent and a surfactant, the surfactant content being W0% based on the total mass of the electrolyte, the hydrophile-lipophile balance value of the surfactant being HLB, and satisfying the following relationship: 80≤D1*ρ*HLB / (100*W0)≤1000.
[0008] In the implementation manner of the present invention, 0<W0≤5, 3≦HLB≦12.
[0009] In the embodiment of the present invention, the thickness of the negative electrode active material layer is D1 μm, 70≦D1≦150.
[0010] In the embodiment of the present invention, the porosity of the negative electrode active material layer is ρ%, 10≦ρ≦40.
[0011] In an embodiment of the present invention, the surfactant includes one or more of stearic acid, sodium dodecylbenzene sulfonate, quaternary ammonium compounds, lecithin, betaine-type compounds, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan, and polysorbate.
[0012] In an embodiment of the present invention, the negative electrode active material layer comprises a first negative electrode active material capable of embedding and extracting sodium ions, and the first negative electrode active material comprises one or more of carbon materials such as hard carbon, natural graphite, artificial graphite, soft carbon, carbon black, acetylene black, carbon nanotubes, graphene, carbon nanofibers, and titanium oxide; and / or,
[0013] The negative electrode active material layer includes a second negative electrode active material capable of alloying with sodium, wherein the second negative electrode active material includes a single substance, oxide or carbide of one or more elements selected from Si, Ge, Pb, In, Zn, Ca, Sr, Ba, Ru and Rh; and / or,
[0014] The negative electrode active material layer includes a third negative electrode active material capable of undergoing a conversion reaction with sodium ions, and the third negative electrode active material includes one or more of a transition metal oxide and a transition metal sulfide.
[0015] In an embodiment of the present invention, the positive electrode includes a positive electrode active material that can extract and embed sodium ions, including one or more of sodium-iron composite oxides, sodium-cobalt composite oxides, sodium-chromium composite oxides, sodium-manganese composite oxides, sodium-nickel composite oxides, sodium-nickel-titanium composite oxides, sodium-nickel-manganese composite oxides, sodium-iron-manganese composite oxides, sodium-nickel-cobalt-manganese composite oxides, sodium-iron phosphate compounds, sodium-manganese phosphate compounds, sodium-cobalt phosphate compounds, sodium-vanadium phosphate compounds, and sodium-vanadium-fluorophosphate compounds.
[0016] In an embodiment of the present invention, the sodium salt comprises one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium bis(oxalatoborate), sodium difluorooxalatoborate, sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl imide), sodium bis(trifluoromethylsulfonyl imide), sodium perchlorate, 4,5-dicyano-2-(trifluoromethyl)imidazol sodium, and 4,5-dicyano-2-(pentafluoroethyl)imidazol sodium. Based on the total mass of the electrolyte, the content of the sodium salt is Ws%, and 5≦Ws≦30.
[0017] In an embodiment of the present invention, the solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, ethylene glycol dimethyl ether, dioxolane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether, and the content of the solvent is W1% based on the total mass of the electrolyte, 50≤W1<90.
[0018] In an embodiment of the present invention, the electrolyte further includes a film-forming additive, and the film-forming additive includes one or more of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, 1-propylene-1,3-sultone, vinyl ethylene carbonate, vinyl sulfate, methylene dicarbonate, tris(trimethylsilyl) phosphate, succinic anhydride, maleic anhydride, etc. Based on the total mass of the electrolyte, the total content of the additive is W2%, 0<W2≤10.
[0019] The present invention introduces a surfactant into the electrolyte and matches the hydrophilic-lipophilic balance value of the selected surfactant with the thickness and porosity of the negative electrode active material layer to promote the infiltration of the electrolyte into the negative electrode active material layer, alleviate the risk of sodium decomposition, increase the discharge capacity and energy density of the battery, and improve the cycle stability. It is also beneficial to reduce battery polarization and improve the battery's rate discharge capability.
[0020] In a second aspect, an embodiment of the present invention further provides an electric device, the electric device comprising the sodium ion battery described in the first aspect. The electric device provided by the embodiment of the present invention comprises the sodium ion battery described in the second aspect, the sodium ion battery has a long cycle life and good rate performance, so that the electric device can be used stably for a long time, which is conducive to improving the performance of the electric device. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.
[0023] Some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0024] Lithium-ion batteries are the most widely commercialized electrochemical energy storage devices. They achieve the conversion of chemical energy and electrical energy through the reversible insertion / extraction of lithium ions between the positive and negative electrodes. Sodium and lithium belong to the same main group, but the reserves of sodium on Earth are much higher than lithium, and my country has abundant sodium resources and sodium extraction technology, so the cost of sodium-ion batteries will be greatly reduced compared to lithium-ion batteries.
[0025] In addition to the advantages of reserves and cost, sodium-ion batteries generate less instantaneous heat in safety tests and have higher safety. In addition, the sodium ion desolvation rate in organic solvents is lower, and under the same conditions, it has a higher ion conduction rate and lower charge transfer impedance. In addition, sodium and aluminum will not form alloys at low potentials, so aluminum can be used as the current collector for both the positive and negative electrodes of sodium-ion batteries to increase the energy density of the battery.
[0026] However, the negative electrode commonly used in sodium-ion batteries currently has the disadvantages of large specific surface area and many surface defects, which will cause the electrolyte to form a thicker SEI on the negative electrode surface and consume more active sodium. In addition, the electrolyte of commercial sodium-ion batteries mainly uses carbonate solvents, which have high viscosity and surface tension and poor wettability to pores, resulting in reduced battery discharge capacity and energy density.
[0027] Based on this, an embodiment of the present invention provides a sodium ion battery, comprising: a positive electrode; a negative electrode, the negative electrode comprising a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer can be coated on one side of the negative electrode current collector or on both sides, and the thickness of the single-layer negative electrode active material layer is D1μm, and the porosity is ρ; an electrolyte, the electrolyte comprises a sodium salt, a solvent and a surfactant, the surfactant content is W0%, the hydrophilic-lipophilic balance value of the surfactant is HLB, and the following relationship is satisfied: 80≤D1*ρ*HLB / (100*W0)≤1000. The hydrophile-lipophile balance (HLB) value of the surfactant (Hydrophile-Lipophile Balance, HLB value for short, quantitatively represents the hydrophilic and hydrophobic properties of the surfactant. The lower the HLB value, the better the lipophilic (organic) property. The turning point of lipophilicity and hydrophilicity is about 10. Near this value, the surfactant molecules have a higher comprehensive hydrophilicity and lipophilicity. For example, paraffin has HLB = 0, which is not hydrophilic; polyethylene glycol has HLB = 20, which is completely hydrophilic) matches the porosity in the negative electrode active material layer, thereby promoting the infiltration of the electrolyte into the pore structure and the capacity of the negative electrode, thereby improving the utilization rate of the active material. D1*ρ is positively correlated with the contact area of electrode / electrolyte, and (100*W0) / HLB is positively correlated with the wetting ability of electrolyte; the greater the thickness and the higher the porosity, the higher the wetting ability of electrolyte is required to ensure sufficient contact and wetting between electrode and electrolyte. The electrode / electrolyte contact area (D1*ρ) and the electrolyte wetting ability ((100*W0) / HLB) need to match to ensure a high ion transport capacity at the electrode / electrolyte interface. During the implementation process, it was found that the value of D1*ρ*HLB / (100*W0) is between 80 and 1000, and the battery has good comprehensive performance. In one embodiment, D1*ρ*HLB / (100*W0) can be 80, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000.
[0028] In one embodiment, 0<W0≤5, 3≦HLB≦12. The hydrophilic-lipophilic balance value HLB of the surfactant reflects the comprehensive affinity of the hydrophilic and lipophilic groups in the surfactant molecule to oil or water. The higher the HLB value, the stronger the hydrophilicity, and vice versa, the stronger the lipophilicity. Surfactant molecules with HLB values between 3 and 12 have better comprehensive hydrophilic and lipophilic abilities. Optionally, the value of HLB can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. As an inert component in the electrolyte, the surfactant can avoid reducing the ion transport capacity of the electrolyte within this content. Optionally, based on the total mass of the electrolyte, the value of W0 can be 0.5, 1, 2, 3, 4, 5.
[0029] In one embodiment, D1 satisfies: 70≦D1≦150. Within this range, the negative electrode can have both a high active material loading and a moderate ion transmission path, thereby ensuring high energy density and fast ion transmission kinetics. Optionally, based on the total mass of the electrolyte, the value of D1 can be 70, 80, 90, 100, 110, 120, 130, 140, 150.
[0030] In one embodiment, ρ satisfies: 10≦ρ≦40. Within this range, the internal porosity of the electrode is moderate, which can not only ensure that the electron transmission channels inside the electrode are closely connected, but also reduce the thickness of the battery cell and increase the volume energy density. Optionally, the value of ρ can be 10, 15, 25, 30, 35, or 40.
[0031] In one embodiment, the surfactant includes stearic acid, sodium dodecylbenzene sulfonate, quaternary ammonium compounds, lecithin, betaine-type compounds, alkyl glucosides, fatty acid glycerides, fatty acid sorbitan, polysorbate, or one or more. The role of surfactants in sodium ion batteries is mainly to reduce the surface tension of the electrolyte, improve the wettability of the electrolyte to the surface of the electrode (the electrode is the positive electrode or the negative electrode), so that the electrolyte can smoothly infiltrate the internal pores of the electrode, promote the embedding and extraction of sodium ions, and be beneficial to the active capacity; especially under high-rate charge and discharge conditions, the improvement of wettability between the electrolyte and the electrode can effectively alleviate the phenomenon of sodium precipitation caused by excessive local sodium ion flux. For example, sodium dodecylbenzene sulfonate is an anionic surfactant, and the anionic functional groups in its molecular structure can be combined with defects and oxygen-containing functional groups on the surface of the negative electrode, and the other end can be complexed with the solvent in the electrolyte, thereby reducing the surface tension of the electrode, promoting the electrolyte to infiltrate the electrode surface and pores, and also can play a certain anti-corrosion role.
[0032] In one embodiment, the negative electrode current collector is aluminum foil. In sodium ion batteries, aluminum foil can be used for both positive and negative electrode current collectors because sodium and aluminum will not react to form alloys, and the cost is much lower than copper foil in lithium batteries. The negative electrode active material layer contains negative electrode active materials that can embed and extract sodium ions. The negative electrode active materials include one or more carbon materials such as hard carbon, natural graphite, artificial graphite, soft carbon, carbon black, acetylene black, carbon nanotubes, graphene, carbon nanofibers, and titanium oxides; and / or, the negative electrode active materials include one or more of Si, Ge, Pb, In, Zn, Ca, Sr, Ba, Ru, Rh, etc., elements that alloy with sodium, oxides containing these elements, and carbides; and / or, the negative electrode active materials include one or more of transition metal oxides and sulfides that can undergo conversion reactions with sodium ions. The negative electrode active materials of sodium ion batteries have the ability to embed and extract sodium ions, which is the key to ensuring that the battery can charge and discharge normally. Among the given negative electrode active materials, carbon materials such as hard carbon, natural graphite, artificial graphite, soft carbon, carbon black, acetylene black, carbon nanotubes, graphene, and carbon nanofibers have good conductivity and plasticity, and can undergo embedding and extraction reactions with sodium ions. These carbon materials can be used alone or in combination in different ways to improve the performance of negative electrode materials. In addition, some metal or non-metallic single substances such as Si, Ge, Pb, In, Zn, Ca, Sr, Ba, etc. can undergo alloying reactions with sodium, and sodium alloys can also undergo dealloying reactions during discharge, thereby realizing the conversion of chemical energy into electrical energy. Therefore, these single substances can also be used as negative electrode materials for sodium ion batteries. In addition, oxides and sulfides containing the above elements can also undergo conversion reactions with sodium ions, and can also be used as negative electrode active materials. Therefore, the negative electrode materials of sodium ion batteries use these materials with different characteristics, aiming to achieve the embedding and extraction of sodium ions through different mechanisms, thereby improving the energy density and cycle life of the battery.
[0033] In one embodiment, the positive electrode of the sodium ion battery includes a positive electrode active material capable of extracting and embedding sodium ions, including sodium iron composite oxide, sodium cobalt composite oxide, sodium chromium composite oxide, sodium manganese composite oxide, sodium nickel composite oxide, sodium nickel titanium composite oxide, sodium nickel manganese composite oxide, sodium iron manganese composite oxide, sodium nickel cobalt manganese composite oxide, sodium iron phosphate, sodium manganese phosphate, sodium cobalt phosphate, sodium vanadium phosphate, sodium vanadium fluorophosphate. One or more of these composite oxides have a variety of crystal structures, such as layered structures, tunnel structures, etc., which are conducive to the embedding and extraction of sodium ions, thereby improving the charge and discharge performance of the battery.
[0034] In one embodiment, the sodium salt comprises one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium bisoxalate borate, sodium difluorooxalate borate, sodium trifluoromethanesulfonate, sodium bisfluorosulfonyl imide, sodium bistrifluoromethanesulfonyl imide, sodium perchlorate, 4,5-dicyano-2-(trifluoromethyl) imidazole sodium, 4,5-dicyano-2-(pentafluoroethyl) imidazole sodium, and the sodium salt is the main electrolyte in the sodium ion battery, which can conduct sodium ions and enable the battery to perform charge and discharge reactions. Based on the total mass of the electrolyte, the content of the sodium salt is Ws%, 5≦Ws≦30. The concentration of the sodium salt has an important influence on the performance of the sodium ion battery. The appropriate concentration of the sodium salt can increase the conductivity of the battery, thereby improving the energy density and charge and discharge performance of the battery.
[0035] Optionally, based on the total mass of the electrolyte, the content of sodium salt in the sodium ion battery electrolyte can be 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 21%, 23%, 25%, 27%, or 30%.
[0036] In one embodiment, the solvent in the sodium ion battery electrolyte includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, ethylene glycol dimethyl ether, dioxolane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether. The solvent can combine with sodium ions to form solvated ions, which helps to stabilize the sodium ions and better transmit them in the electrode material. Based on the total mass of the electrolyte, the content of the solvent is W1%, 50≤W1<90. Optionally, the content of sodium salt in the sodium ion battery electrolyte can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%.
[0037] In one embodiment, the electrolyte further includes a film-forming additive, and the film-forming additive includes one or more of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, 1-propylene-1,3-sultone, vinyl ethylene carbonate, vinyl sulfate, methylene dicarbonate, tris(trimethylsilyl)phosphate, succinic anhydride, and maleic anhydride. Some additives can increase the conductivity of the electrolyte, thereby accelerating the transmission speed of electrons and ions, improving the charge and discharge performance of the battery, inhibiting side reactions and adjusting interface properties, thereby improving the electrochemical properties of the electrode. Based on the total mass of the electrolyte, the total content of the additive is W2%, 0<W2≤10. Optionally, the content of sodium salt in the sodium ion battery electrolyte can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0038] The embodiment of the present invention further provides an electric device, which includes the sodium ion battery in any of the above embodiments. Specifically, the electric device can be an electric car, an electric motorcycle, an electric bicycle, a mobile power supply, an unmanned aerial vehicle, a mobile phone, a computer, a camera, an electric tool, a smart home or a wearable device.
[0039] The electric device provided in the embodiment of the present invention comprises a sodium ion battery, which has a long cycle life and good rate performance, so that the electric device can be used stably for a long time, which is beneficial to improving the performance of the electric device.
[0040] The technical solution of the present invention is further illustrated below through specific embodiments and comparative examples.
[0041] Example 1
[0042] (1) Preparation of electrolyte
[0043] In an argon atmosphere glove box with a water content of <1ppm and an oxygen content of <1ppm, propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of 4:4:2, a surfactant was added, and then NaPF6 was added to prepare an electrolyte with a NaPF6 concentration of 1 mol / L. The types and contents of the surfactants are shown in Table 1.
[0044] (2) Preparation of positive electrode
[0045] The positive electrode active material sodium manganese composite oxide (NaMnO2), the conductive agent carbon nanotube (CNT), and the binder polyvinylidene fluoride are mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added. The mixture is stirred into a uniform positive electrode slurry under the action of a vacuum mixer, and then the positive electrode slurry is evenly coated on the positive electrode current collector Al foil; after drying at 85°C, it is cold pressed, cut into pieces, and slit, and then dried under vacuum conditions at 85°C for 4 hours to obtain a positive electrode sheet.
[0046] (3) Negative electrode preparation
[0047] The negative electrode active material hard carbon, the conductive agent acetylene black, the binder SBR: the dispersant CMC were fully stirred and mixed in a deionized water solvent system at a mass ratio of 93.5:2:2.5:2, and then coated on Al foil, dried, and cold pressed to obtain a negative electrode sheet. The porosity and thickness of the negative electrode sheet are shown in Table 1.
[0048] (4) Diaphragm preparation
[0049] The diaphragm is made of polypropylene.
[0050] (5) Preparation of sodium ion batteries
[0051] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound and placed in an outer packaging foil. The prepared electrolyte is injected into the dried electrode core, and after vacuum packaging, standing, formation, shaping and other processes, the preparation of the sodium ion battery is completed.
[0052] Embodiments 2 to 16
[0053] The types and contents of surfactants, thickness and porosity of negative electrode sheets of Examples 2 to 16 are shown in Table 1, and the remaining steps are the same as those of Example 1.
[0054] Comparative Examples 1 to 10
[0055] The types and contents of surfactants, thickness and porosity of negative electrode sheets of Comparative Examples 1 to 10 are shown in Table 1, and the remaining steps are the same as those of Example 1.
[0056] Table 1 Negative electrode active material layer and surfactant selection
[0057]
[0058]
[0059] Test method:
[0060] (1) Normal temperature cycle test
[0061] Take the prepared sodium ion battery and charge it to 3.95V at a constant current of 0.5C at room temperature (25±3℃), then charge it to 0.05C at a constant voltage at 3.95V, let it stand for 5min, and then discharge it to 1.5V at a constant current of 0.5C, let it stand for 5min, which is one cycle. Record the capacity retention rate (ratio of discharge capacity after 1000 cycles to discharge capacity in the first cycle) and thickness expansion rate (1000 full-charge thickness / first full-charge thickness) after 1000 cycles at room temperature. The cycle uses a NEWARE test cabinet (model CTE-4080D-5V30A). To ensure that the battery temperature is constant during the cycle test, the battery is placed in a high and low temperature test box (model CH1000T). The battery thickness test uses a PPG tester (model ATMPPGSH200).
[0062] (2) Low temperature (12 degrees Celsius) cycle test
[0063] The prepared sodium ion battery was charged to 3.95V at 0.5C rate at 12 degrees Celsius (12±3℃), then charged to 0.05C at 3.95V, left for 5 minutes, and then discharged to 1.5V at 0.5C rate, left for 5 minutes, which was considered a cycle. The capacity retention rate after 600 low-temperature cycles was recorded.
[0064] (3) Normal temperature rate test
[0065] Take the prepared sodium ion battery at room temperature (25±3℃) and charge it to 3.95V at 0.2C rate constant current and constant voltage, cut off at 0.05C, let it stand for 5min, then discharge it to 1.5V at 0.2C rate constant current and let it stand for 5min, which is one cycle. After two 0.2C cycles, the second cycle discharge capacity is taken as the 0.2C discharge capacity. Then the battery is charged to 3.95V at 0.5C rate constant current and constant voltage, cut off at 0.05C, let it stand for 5min, then discharge it to 1.5V at 2C rate constant current and let it stand for 5min, which is one cycle. After two 2C cycles, the second cycle discharge capacity is taken as the 2C discharge capacity. The ratio of the discharge capacity recorded twice is the room temperature 2C / 0.1C capacity retention rate.
[0066] (4) Low temperature circulation sodium precipitation
[0067] The battery was disassembled in a fully charged state after 600 cycles of low-temperature cycling, and the sodium precipitation on the surface of the negative electrode was observed. If there was obvious silvery-white metallic product deposition on the large surface, tab or crease of the negative electrode, it was considered as sodium precipitation. In the case of severe sodium precipitation, the sodium metal will react with the electrolyte to cause the sodium metal to change from silvery white to yellow.
[0068] Table 2 Cycle test and sodium precipitation test results
[0069]
[0070] It can be seen from Table 1 and Table 2 that, specifically, by comparing Examples 1 to 16 and Comparative Examples 1 to 10, when the thickness, porosity, surfactant content and hydrophile-lipophile balance value of the negative electrode active material layer meet the range of 80≤D1*ρ*HLB / (100*W0)≤1000 described in the present invention, the room temperature cycle performance, low temperature cycle performance and rate cycle performance are excellent, and no sodium precipitation occurs. The negative electrode sheet as a whole presents a uniform gray-black morphology, and there is no obvious silvery white or yellow by-product deposition.
[0071] From the above test results, it can be concluded that when the thickness of the negative electrode active material layer is large and the porosity is high, the electrolyte needs to have higher wettability. The lower the HLB value of the surfactant in the electrolyte, the higher the content W0, and the better the wetting effect. When D1*ρ*HLB / (100*W0)>1000, it means that the porosity D1*ρ / 100 in the negative electrode active material layer is too large, exceeding the total wetting capacity W0 / HLB of the surfactant additive in the electrolyte. The wettability of the electrolyte to the electrode is not enough, and the microporous area not wetted by the electrolyte is difficult to contribute to the active capacity, resulting in a low total discharge capacity of the whole battery. More seriously, it will cause the sodium ions released from the positive electrode to be unable to enter the active area of the negative electrode and thus deposit on the surface, causing sodium precipitation and safety hazards. For example, in Comparative Example 2, there is obvious silver-white metallic sodium deposition at the crease of the negative electrode sheet after low-temperature cycling. When D1*ρ*HLB / (100*W0) is less than 80, such as in Comparative Examples 3 to 10, excessively high proportions of surfactants are gathered on the positive and negative electrode surfaces, which indeed improves the wettability of the electrolyte to the electrodes, but the inert adsorption layer prevents the sodium ions from contacting the positive and negative electrode active materials, hindering ion / electron transmission, increasing the battery polarization, and reducing the rate discharge capacity. In addition, due to the poor oxidation stability of the surfactant, the surfactant will undergo irreversible oxidative decomposition on the positive electrode surface, and the side reaction will cause the current in the charging process to be unable to be reduced to below the constant voltage cutoff current. The accumulation of side reaction products on the positive electrode side will further increase the positive electrode impedance, increase polarization, and further reduce the positive electrode active capacity. On the other hand, excessive accumulation of surfactant molecules on the surface of the negative electrode will prevent sodium ions from entering the interior of the negative electrode, but instead they gain electrons on the surface for reduction, resulting in sodium precipitation at the negative electrode. For example, in Comparative Example 4, after low-temperature cycling, the negative electrode sheet exhibits large-area sodium precipitation, and irreversible redox reactions occur between sodium metal and electrolyte solvent and additive molecules, resulting in the accumulation of side reaction products. A large amount of silver-white and brown-yellow reaction products accumulate on the surface of the negative electrode sheet, and the highly active sodium catalyzes the reduction of the electrolyte to produce gas, and the continued growth of sodium dendrites may puncture the diaphragm, causing battery short circuits and serious safety problems.
[0072] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A sodium ion battery, characterized in that: The sodium ion battery comprises: A positive electrode; a negative electrode, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer is disposed on the negative electrode current collector, and wherein the thickness of the negative electrode active material layer is D1 μm and the porosity is ρ%; An electrolyte, the electrolyte comprising a sodium salt, a solvent and a surfactant, based on the total mass of the electrolyte, the content of the surfactant is W0%, the hydrophile-lipophile balance value of the surfactant is HLB, and satisfies the following relationship: 80≤D1*ρ*HLB / (100*W0)≤1000.
2. The sodium ion battery according to claim 1, characterized in that The W0 satisfies: 0<W0≤5, and the HLB satisfies: 3≦HLB≦12.
3. The sodium ion battery according to claim 1, characterized in that: The D1 satisfies: 70≦D1≦150.
4. The sodium ion battery according to claim 1, characterized in that The ρ satisfies: 10≦ρ≦40.
5. The sodium ion battery according to claim 1, characterized in that: The surfactant includes one or more of stearic acid, sodium dodecylbenzene sulfonate, quaternary ammonium compounds, lecithin, betaine compounds, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan, and polysorbate.
6. The sodium ion battery according to claim 1, characterized in that: The negative electrode active material layer comprises a first negative electrode active material capable of embedding and extracting sodium ions, wherein the first negative electrode active material comprises one or more carbon materials such as hard carbon, natural graphite, artificial graphite, soft carbon, carbon black, acetylene black, carbon nanotubes, graphene, carbon nanofibers, and titanium oxide; and / or, The negative electrode active material layer includes a second negative electrode active material capable of alloying with sodium, wherein the second negative electrode active material includes a single substance, an oxide or a carbide of one or more elements selected from Si, Ge, Pb, In, Zn, Ca, Sr, Ba, Ru and Rh; and / or, The negative electrode active material layer includes a third negative electrode active material capable of undergoing a conversion reaction with sodium ions, and the third negative electrode active material includes one or more of a transition metal oxide and a transition metal sulfide.
7. The sodium ion battery according to claim 1, characterized in that: The sodium salt comprises one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium bisoxalatoborate, sodium difluorooxalatoborate, sodium trifluoromethylsulfonate, sodium bisfluorosulfonyl imide, sodium bistrifluoromethylsulfonyl imide, sodium perchlorate, 4,5-dicyano-2-(trifluoromethyl)imidazole sodium, and 4,5-dicyano-2-(pentafluoroethyl)imidazole sodium. Based on the total mass of the electrolyte, the content of the sodium salt is Ws%, and 5≦Ws≦30.
8. The sodium ion battery according to claim 1, characterized in that: The solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, ethylene glycol dimethyl ether, dioxolane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether. Based on the total mass of the electrolyte, the content of the solvent is W1%, 50≤W1<90.
9. The sodium ion battery according to claim 1, characterized in that: The electrolyte also includes a film-forming additive, which includes one or more of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, 1-propylene-1,3-sultone, vinyl ethylene carbonate, vinyl sulfate, methylene dicarbonate, tris(trimethylsilyl) phosphate, succinic anhydride, and maleic anhydride. Based on the total mass of the electrolyte, the total content of the film-forming additive is W2%, 0<W2≤10.
10. An electrical device, characterized in that: A sodium ion battery comprising the sodium ion battery according to any one of claims 1 to 9.
Citation Information
Cited By
Sodium ion battery monomer, battery device and power utilization device
CN121123367A
A sodium-ion battery cell, battery device, and power-using device
CN121123367B
Sodium ion battery monomer, battery device and electric equipment
CN121583991A